Resonant Scattering and Energy Relaxation in Quantum Dot Systems - I. A. Larkin; A. Vagov (Advances in Condensed Matter Physics)
We propose a new Auger-like mechanism for energy relaxation in quantum dots (QD) driven by resonant scattering of delocalized wetting layer (WL) carriers. It is demonstrated that resonant scattering leads to a considerable increase in the relaxation rate that can explain experimentally obtained relaxation rates. Analytical results for the relaxation rate are obtained for rectangular dots revealing a weak logarithmic dependence on the dot depth and level density. Comparing results for a rectangular and a parabolic QD model we conclude that the relaxation rate is not very sensitive to a chosen model.